The use of microarrays to understand the biology and toxicology of low dose arsenic - Hamilton, Joshua (Henry Stewart Talks, 2009)
Arsenic as an environmental chemical of concern for human health, Use of microarrays to understand patterns of gene expression changes in response to low levels of toxic metals, Development of non-parametric techniques for evaluating results of microarrays, Use of patterns and biological pathways to understand microarray results, Microarray analysis of low dose arsenic effects
Archived at 2021/02/25